Primena daljinske detekcije u inventuri mešovitih šuma hrasta lužnjaka - Borota Dragan; Pantić Damjan; Ponjarac Radenko; Popović Aleksandar (Glasnik Šumarskog Fakulteta: Univerzitet u Beogradu)
In high, mixed, middle-aged and maturing Penduculate oak stands, the possibility of using aerial photogrammetry in the inventory was tested, both to obtain information related to site and stand information and to determine numerical elements (number of trees, basal area and volume per hectare) obtained on the basis of data read from the images (crown diameter, height and estimated breast height diameter of the tree based on the selected mathematical model). Most of the information from the site and stand information, especially the information about the above-ground parts of the forest (presence of dead cover, ground vegetation, shrubs, weeds, saplings and the degree of their damage, etc.) could not be identified from the image. There was a significant difference in the average number of trees, basal area of stands and stand volume per hectare determined on the basis of aerial image data, compared to the values determined by the terrestrial survey. In middle-aged stands, the number of trees determined from aerial image is 21.5 % higher and in maturing stands 9.5 % lower than the values determined by a total measurement. In middle-aged stands, the basal area AP-1 is 13.5 % higher and AP-2 15.6 % higher than the values determined in the total measurement. In the maturing stands, these deviations are 13.1 % and 3.7 %. The stand volume is the element with the greatest deviations compared to the total measurement. In middle-aged stands the difference is 31 % and 28.1 %, and in maturing stands 37.9 % in AP-1 and even 67.1 % in AP-2. The reasons for the impossibility of a precise interpretation of most of the information related to the information of the site and the stand and for the significant differences in the numerical elements compared to the total measurement lie in the broad and intertwined crowns (dense canopy closure) of the oaks in the upper storey and in the vertical structure of these mixed stands. The results obtained exclude the use of aerial photogrammetry in the inventory of this certain forests, as it does not provide a reliable information basis for the development of realistic forest management plans. Possible applications exist in distinguishing of land use, locating fire areas, areas affected by hurricanes and other disasters, etc., and even in the inventory of pure stands with low canopy closure.